Laparoscopic resection of gastric schwannoma: A case report. (2019) - Cordera, Fernando; Salazar-Vitale, Andrea; Mejía-Sánchez, Estephany; Arrangoiz, Rodrigo; Caba-Molina, David; Muñoz-Juárez, Manuel; Luque-de-León, Enrique; Moreno-Paquentín, Eduardo
Highlights: This is one of only 220 cases of reported cases of gastric Schwannoma. This is one of the very few cases of these rare tumors that has been managed with a laparoscopic approach. We present images of the preoperative evaluation (CT) and of the laparoscopic approach (intraoperative photos). The patient has over a one-year follow-up and the patient is in perfect condition with no evidence of disease. We accompany the case report with a thorough current review on this subject. Abstract: Introduction: Gastric schwannomas are an extremely rare presentation of mesenchymal tumors originating from Schwann cells, accounting for 0.2% of all gastric tumors. Patients are usually asymptomatic, so these tumors are frequently detected incidentally. Presentation of case: 68-year old male patient found to have a 5 cm mass in the lesser curvature of the stomach. After a careful preoperative evaluation, complete laparoscopic resection was performed. Pathology review confirmed a completely resected gastric Schwannoma. The patient's recovery was uneventful. At a one-year follow-up he remains asymptomatic and with no evidence of disease. Discussion: We present the uncommon case of a gastric schwannoma that was appropriately treated with a laparoscopic approach and present a current literature review focusing on diagnostic and treatment methods of these rare tumors. Conclusion: Schwannomas should be included in the differential diagnosis of gastric tumors and can be appropriately treated with a laparoscopic approach.